The Role of Academic Resilience in Online Learning: Systematic Literature Review - Paulina Kurniadi; Talitha Lintang Pertiwi; Kholifah Umi Sholihah; Dian Ratna Sawitri (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
During the COVID-19 pandemic, lectures are held using online platforms. The online courses are challenging for students. To face these challenges, students need academic resilience. This study aimed to determine the role of academic resilience in students during online learning. This study uses a systematic literature review method by reviewing research articles from 2012-2021 published in Crossref, Google Scholar, and Scopus. The key words used to extract records were: “Academic Resilience” AND “Online Learning” OR “E-Learning” AND “Students” OR “College” OR “University”. All 904 articles were filtered using the Rayyan application, and 11 relevant articles were extracted for further review. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was used for the study design. The characteristics of the articles reviewed are in English, research participants are students, use quantitative and qualitative research designs, and focus on students' academic resilience in online learning. From the 11 articles reviewed, it was concluded that academic resilience appears to play an essential role in online learning. Academic resilience enables students to have higher motivation in overcoming difficulties faced in the online course, be able to survive under pressure and be able to find the solutions to academic problems, demonstrate better academic performance, easily bounce back, plan the learning process, show greater involvement and academic achievement, as well as explore relevant information during online course. In addition, academic resilience is more likely to improve social competence and academic adjustment.